Real and Monetary Challenges to Wage Policy in Germany at the Turn of the Millennium: Technical Progress, Globalization and European Monetary Union - Wolfgang Franz (Center for Economic Studies and ifo Institute (CESifo), 1999)
At the turn of the millennium three frequently cited potential causes of new challenges for wage p olicy in Germany are revisited in this study: skilled-biased technological progress, the increasing international integration of labor and product markets, and the monetary integration of the EMU. While there is now a fairly broad consensus on the basic fa cts about the development of wages and employment across skill groups, there is considerable disagreement to explain these trends, in particular to what extent skill-biased technical change and trade liberalization share a major responsibility. The conclusion of this paper is that both factors are at work with a slight emphasis on the first candidate. Moreover, while EMU in our opinion does not represent the major threat for wage policy, it is the Single Market which requires wage policy to be on the lookout and to meet those challenges.Monetary Union
Keywords: 330; Wages; wage structure; skill-biased technological change; international trade; European Monetary Union; globalisation; globalization